2020
DOI: 10.1186/s12873-020-00340-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of peripheral vascular access in the prehospital setting: is there room for improvement?

Abstract: Background: Previous studies have shown that prehospital insertion of peripheral vascular access is highly variable. The aim of this study is to establish the proportion of peripheral vascular access placement and its use with regard to both the severity of cases and the main problem suspected by the paramedics involved. Over-triage was considered to have taken place where peripheral vascular access was placed but unused and these cases were specifically analysed in order to evaluate the possibility of improvi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…The prevalence of prehospital IV access was higher in CTAS level 1 patients compared to CTAS level 2 patients and in trauma cases compared to medical cases. Our findings are consistent with a Swiss study that reported peripheral vascular access placement in 26% of cases transported [ 15 ]. Another study conducted in the United States in 2014 focused on the prehospital management of patients with severe sepsis and found that 23% received prehospital IV catheter and fluid administration, while 7% had a catheter alone, and 70% had neither a catheter placed nor fluid administered [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of prehospital IV access was higher in CTAS level 1 patients compared to CTAS level 2 patients and in trauma cases compared to medical cases. Our findings are consistent with a Swiss study that reported peripheral vascular access placement in 26% of cases transported [ 15 ]. Another study conducted in the United States in 2014 focused on the prehospital management of patients with severe sepsis and found that 23% received prehospital IV catheter and fluid administration, while 7% had a catheter alone, and 70% had neither a catheter placed nor fluid administered [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Comparing that with another study conducted in France on the feasibility of IV line placement, the figure was only 29% [ 22 ]. In this study, we found that half of the prehospital IV lines were unutilized, which is closely comparable to a study in Switzerland in which 45.9% were unutilized [ 15 ]. Furthermore, we found that most CTAS level 1 patients had their IV access utilized.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Over-use of peripheral vascular access in regions where paramedics conduct prehospital care has been reported in another study. 18 Finally, both the MMT and PIT perform many non-urgent interventions. It has also been recognized in other studies that non-urgent prehospital interventions have increased in all European countries.…”
Section: Discussionmentioning
confidence: 99%
“…A global multicentre point prevalence study revealed widespread problems with PIVCs, including idle catheters (no indication for use), missing documentation in patient records, devices placed in non‐recommended sites of flexion such as the wrist or antecubital fossa and phlebitis and other PIVC malfunctions such as extravasation and leakage (Alexandrou et al., 2018). Nearly half of the PIVCs inserted in the prehospital setting remain idle (Gonvers et al., 2020), and emergently inserted catheters in a non‐aseptic environment are associated with later development of sepsis or BSI (Hughes et al., 2014). The incidence of BSIs due to PIVCs may represent 4.8%–19% of hospital‐acquired bacteraemia (Mermel, 2017).…”
Section: Introductionmentioning
confidence: 99%